The planarity of the stick and arm motion in the field hockey hit - Willmott, A.; Dapena, J. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The development of relevant simulation models is one way in which our knowledge of the field hockey hit may be improved. The aim of this study was to test the appropriateness of a planar pendulum model for the motion of the stick and arms during the downswing. The hits of 13 experienced female players were filmed, and swing planes were fitted to the motion of the stickface during the downswing. Low variability in the length of a segment`s projection onto the swing plane was taken as evidence for the validity of a planar model. Coefficients of variation of less than 5% for the stick and forearm lengths supported the use of such a model for these segments, but its validity for the upper arms is less certain.